Three-Dimensional Refined Numerical Modeling of Artificial Ground Freezing in Metro Cross-Passage Construction: Thermo-Mechanical Coupling Analysis and Field Validation - Qingzi Luo; Junsheng Li; Wei Huang; Wanying Wang; Bingxiang Yuan (Buildings)
The artificial ground freezing method (AGF) is widely used in underground construction to reinforce the ground and ensure construction safety. This study systematically evaluates the implementation of the artificial ground freezing method in the construction of a metro tunnel cross-passage, with a focus on analyzing the soil’s thermo-mechanical behavior and assessing safety performance throughout the construction process. A combined approach integrating field monitoring and refined three-dimensional numerical simulation using FLAC3D is adopted, considering critical factors, such as freezing pipe inclination, thermo-mechanical coupling, and ice–water phase transitions. Both field data and simulation results demonstrate that increasing the density of freezing pipes accelerates temperature reduction and intensifies frost heave-induced displacements near the pipes. After 45 days of active freezing, the freezing curtain reaches a thickness of 3.7 m with an average temperature below −10 °C. Extending the freezing duration beyond this period yields negligible improvement in curtain performance. Frost heave deformation develops rapidly during the initial phase and stabilizes after approximately 25 days, with maximum vertical displacements reaching 12 cm. Significant stress concentrations occur in the soil adjacent to the freezing pipes, with shield tunnel segments experiencing up to 5 MPa of stress. Thaw settlement is primarily concentrated in areas previously affected by frost heave, with a maximum settlement of 3 cm. Even after 45 days of natural thawing, a frozen curtain approximately 3.3 m thick remains intact, maintaining sufficient structural strength. The refined numerical model accurately captures the mechanical response of soil during the freezing and thawing processes under realistic engineering conditions, with field monitoring data validating its effectiveness. This research provides valuable guidance for managing construction risks and ensuring safety in similar cross-passage and cross-river tunnel projects, with broader implications for underground engineering requiring precise control of frost heave and thaw settlement.